The Routledge history of antisemitism
1 online resource
Keywords: "Antisemitism is a topic on which there is a wide gap between scholarly and popular understanding, and as concern over antisemitism has grown, so too has the debates over how to understand and combat it. This handbook explores its history and manifestations, ranging from its origins to the internet. Since the Holocaust, many in North America and Europe have viewed antisemitism as a historical issue with little current importance. However, recent events show that antisemitism is not just a matter of historical interest or of concern only to Jews. Antisemitism has become a major issue confronting and challenging our world. The volume starts with explorations of antisemitism in its many different shapes across time and then proceeds to a geographical perspective, covering a broad scope of experiences across different countries and regions. The final part discusses the manifestations of antisemitism in its varied cultural and social forms. With an international range of contributions across 40 chapters, this is an essential volume for all readers of Jewish and non-Jewish history alike"--